Acetone as a Modulator of Surfactant Behavior in Mixed Solvents: Surface Tension, Viscosity, and Micellization - Shah, Sujit Kumar; Bhattarai, Geeta; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2025)
This study investigates the influence of acetone on the physicochemical characteristics of surfactants, focusing on surface tension, viscosity, and micellization behavior in acetone-water mixtures. The critical micelle concentration (CMC) of Sodium dodecyl sulfate (SDS) and Cetyltrimethylammonium bromide (CTAB) increases with acetone content, reflecting weaker hydrophobic interactions due to the reduced dielectric constant of the mixed solvent. Surface tension measurements reveal decreased surfactant efficiency in acetone-rich environments, while viscosity data indicate enhanced solute-solvent interactions, as evidenced by rising  values. These changes are attributed to acetone’s disruption of water’s hydrogen-bond network, altering interfacial dynamics and micelle formation.